(untitled) (Bangladesh Journal of Child Health, 2014)
Introduction: Seizures are quite common in newborn babies. Among other investigations, EEG is used to show the type and location of the activity in the brain during a seizure. Correlation between clinico-etiological profile of neonatal seizures and EEG findings, so far, has not been studied in Bangladesh. Objective: The objective of the study was to correlate the clinical, etiological and EEG profile of neonatal seizures. Methodology: It was a cross-sectional study done at NICU of BSMMU and Central Hospital Ltd. All the neonates admitted with seizures during the study period were included in the study. Their clinico-etiological profiles were carefully recorded and EEG were done in all the cases. Chi-square test was done to find out the statistical difference. Results: Among total 51 cases of neonatal seizures, 29 (56.86%) cases had perinatal asphyxia, followed by septicemia in 8 (15.67%) and meningitis in 6 (11.76%). Hypoglycemia and hypocalcaemia was found in 10 (19.6%) & 8 (15.7%) cases respectively and 15 (29.4%) had acidosis. Thirty seven (72.5%) patients had seizure within 3rd day of life. Seizures were found tonic in nature in 23(45.1%) cases and subtle 18 (35.3%) cases. EEG findings were abnormal in 22 (43.1%) cases. EEG findings were analyzed with the etiology of seizures and it was found that there was a significant relationship between EEG changes and perinatal asphyxia (p<.0001), septicemia (p<.05), meningitis (p<.01) and neurometabolic disorder (p<.0001). However, no statistical significant relationship between type of discharges of EEG and type (p>.05) & pattern of seizures (p>.05) was found. Conclusion: This study suggests that there is a significant statistical relationship between EEG findings with perinatal asphyxia, septicemia and meningitis, but no relationship with types and pattern of seizures. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20023 Bangladesh J Child Health 2014; VOL 38 (1) : 19-23